S. M. Shirokogoroff's book Sociаl Organization of the Northern Tungus and its Russian translation: history, structure, and interpretations. Issue 1 (2nd January 2016) - Sirina, Anna Anatol'evna; Davydov, Vladimir Nikolaevich; Povoroznyuk, Olga Alekseevna; Simonova, Veronika Vital'evna
Abstract : S. M. Shirokogoroff's book Social Organization of the Northern Tungus was originally published in 1929 in English and later also in Chinese and Japanese languages. It is striking that this monograph has still not been published in Russian. It contains rich ethnographic data on Evenki kin relations, family organization, property relations, and various customs regulating social life. This text demonstrates how ethnographic data are translated into a theory. Compared to the Russian texts of the same period, S. M. Shirokogoroff's writings were free from Soviet ideological frames. This article discusses the historical and ideological contexts, in which Alexsandr Nikolaevich Gorlin (1878–1939), a literary translator, worked on the Russian translation of S. M. Shirokogoroff's book in the 1930s, as well as the challenges that the contemporary readers and academic editors of the translation face. It shows that the translation process itself and translation versions are intriguing objects of anthropological research, as they illustrate the temporal dimension of the academic language and facilitate our understanding and interpretation of diverse processes that molded the indigenous peoples' image in the early Soviet science.